2013
DOI: 10.1039/c3nr00184a
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Pt nanocatalysts for the aerobic selox of cinnamyl alcohol

Abstract: The selective aerobic oxidation of cinnamyl alcohol over Pt nanoparticles has been tuning via the use of 5 mesoporous silica supports to control their dispersion and oxidation state. High area two-dimensional SBA-15, and three-dimensional, interconnected KIT-6 silica significantly enhance Pt dispersion, and thus surface PtO 2 concentration, over that achievable via commercial low surface area silica. Selective oxidation activity scales with Pt dispersion in the order KIT-6 ≥ SBA-15 > SiO 2 , evidencing surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 50 publications
(88 reference statements)
6
30
0
Order By: Relevance
“…mesopores for KIT-6 [48], and the incorporation of 300 nm macropores between hexagonal close-packed mesopore channels in MM-SBA-15 [50]. Physicochemical characteristics of the Pt/silica analogues are summarised in Table S2, and are in excellent agreement with literature reports [32,51,52]. XRD, HRTEM and N2 porosimetry confirmed retention of the parent silica pore structures following platinum impregnation (Table S2, Figure S3-4), but a loss of BET surface area and pore volume proportional to Pt loading, attributed to partial pore blockage, as previously observed.…”
Section: Characterisationsupporting
confidence: 84%
See 1 more Smart Citation
“…mesopores for KIT-6 [48], and the incorporation of 300 nm macropores between hexagonal close-packed mesopore channels in MM-SBA-15 [50]. Physicochemical characteristics of the Pt/silica analogues are summarised in Table S2, and are in excellent agreement with literature reports [32,51,52]. XRD, HRTEM and N2 porosimetry confirmed retention of the parent silica pore structures following platinum impregnation (Table S2, Figure S3-4), but a loss of BET surface area and pore volume proportional to Pt loading, attributed to partial pore blockage, as previously observed.…”
Section: Characterisationsupporting
confidence: 84%
“…Nevertheless, the nature of the active site and role(s) of promoters and base remain poorly understood, reflecting the complex solid-liquid-gas interface and necessity for (but attendant difficulties in performing and interpreting) in-situ/operando studies on supported metal catalysts for aerobic selox [30,31]. Recent spectroscopic and kinetic studies of cinnamyl alcohol aerobic oxidation over silica supported Pt nanoparticles identified surface PtO2 as the active site for the selective production of cinnamaldehyde [32].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [15], Scott et al [16] and Hara et al [17] have likewise reported a heterogeneous Pd(II) active species responsible for aerobic alcohol selox, while homogeneous Pd(II) complexes are well known to catalyse such alcohol oxidations [18], [19] and [20]. Interestingly, surface PtO2 has also been recently reported as the active phase in the analogous Pt catalysed aerobic selox of allylic alcohols [21].…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic advantage of spatially segregating Pt NPs within mesopores, accessible overwhelmingly only through interconnected macropores containing Pd NPs, was explored for the cascade oxidative dehydrogenation of cinnamyl alcohol  cinnamaldehyde  cinnamic acid, the latter an important flavorant and essential oil 21,22 . Pd is highly selective for catalyzing cinnamyl alcohol oxidation to cinnamaldehyde 23,24 , but promotes decarbonylation of the resultant aldehyde product; in contrast, Pt favours undesired hydrogenation of cinnamyl alcohol (via reactively-formed surface hydrogen) to 3-phenylpropionaldehyde 25 , but is highly selective towards cinnamaldehyde oxidation to the desirable cinnamic acid product 26 . An optimal catalyst design would therefore ensure that cinnamyl alcohol was oxidized over Pd prior to encountering Pt sites, while permitting the reactively-formed cinnamaldehyde to subsequently access Pt sites for the selective production of cinnamic acid in the second oxidation step.…”
mentioning
confidence: 99%